THE MULTIPLE ROLES OF HEANEY’S LANDSCAPES: A MIRROR OF LIFE AND ITS DILEMMA - Tneh, David C. E. (Sanata Dharma University, 2018)
This paper discusses the timeless appeal of the poetry of Seamus Heaney, the poet laureate of Ireland and Nobel Prize winner for literature (1995). This paper traces the early developments of Heaney’s poetry and highlights how the creative genre offers a dialogic platform (even in the 21st century) for national and political issues. Heaney’s poetry transcends geographical boundaries with its evocative imagery and fluidity of time and space that is alluring, enigmatic, and striking. This paper will then discuss how multiple roles of Heaney’s metaphorical landscapes from his five collections of poetry (from 1966 to 1979) namely Death of a Naturalist, Door into the Dark, Wintering Out, North, and Fieldwork are not merely poems about the nature, the environment, and Ireland but are instruments about his socio-economic/political views concerning idyllic Irish rural life, memories, nationalism, sectarian violence, colonial British rule, and his Catholic faith. The discussion of his selected poetry offers a deep intimate insight of Heaney’s earlier poetry that mirrors Irish life and its struggles with nationhood. DOI: https://doi.org/10.24071/ijhs.2018.010202